Caracterização elementar e análise da resistividade elétrica superficial de pigmentos usados em tatuagem - Lacerda, Camila Munhoz (2017)
The practice of tattooing is a widely spread procedure in society and, even though it’s been surrounded by modern techniques, some concerns are relevant to procedures that involve some health risk. In the current research samples of pigments were analyzed and used to perform tattoos in order to evaluate the metals present in their composition. Besides to correlate the presence of these metals with possible pathologies. In addition to the verification of the variation in the electrical surface resistivity values in the place where the pigment is tattooed, when compared to the material without the ink. For the pigments elementary characterization, the energy dispersion X-ray fluorescence spectroscopy (EDXRF) technique was used, which allows qualitative and quantitative analyses of the results. Two EDXRF specific techniques were used to analyze the elements present in the samples, which were elaborated specifically for the research, together with a last method for the elementary characterization denominated dispersive energy spectroscopy (DES), which uses the Electron Microscopy of Scanning (EMS). All the aforementioned equipment were used to evaluate the metals present in the constitution of the analyzed pigments. After the first step of analysis, referring to the elementary characterization, the second one was applied to analyze the different values of surface electrical resistivity of the ink samples, when injected in synthetic surfaces called artificial skins. Since the own tattoo paints contain discovered metals in the first step of research, which give them different colors, at that second step the electrical conductivity were measured and compared with defined metals at the first step. Analyzed electrical surface resistivity of the synthetic skin can be reduced due to the presence of the metals in the paints and, therefore, the material that was insulator happens to conduct electric current when submitted to conditions suitable for the appearance of the current, producing a favorable situation for the heat generation by Joule effect, which could cause burns or lesions in the region where the pigment is deposited. The use of mentioned techniques confirmed the presence of some metals in studied samples of tattoo paints and it was possible to conclude that, due to the fundamental characteristics of discovered and identified metals, the electrical resistivity in the tattooed artificial skins was altered. Thus, it was verified the relevance of conducted research in order to contribute for the future studies of health hazard related to tattoos ink.